Nursing Care for Patients with Animal Bites that Transmit Rabies - Wulandari, Ning Arti; Romadhon, Wimar Anugerah; Lestari, Oni Puji (Health Gate, 2025)
Rabies is a disease caused by the Ribonucleic Acid (RNA) virus from the Rhabdoviridae family, a neurotropic, highly contagious, bullet-shaped virus. Analyzing an overview of case studies in providing nursing care to patients with bites from animals that transmit rabies in the emergency unit of the Kepanjenkidul Health Center, Blitar City. This case study was carried out on 4 patients who were bitten by rabies-transmitting animals, who had received nursing care in accordance with Indonesian nursing care standards and were evaluated on the 7th day after the bite. The results of the case study show that from the four cases nursing diagnoses emerged of impaired skin/tissue integrity, acute pain, risk of infection with nursing interventions including pain management, wound care, and infection prevention. All implementations were carried out in accordance with planning, the results of the evaluation on the seventh day all nursing care goals were achieved and there were no further complications. There is a need to socialize standards for management of rabid animal bites and improve coordination between health workers and related agencies to immediately carry out mitigation